IN SILICO STUDY OF MIRNA-REGULATED IQ MOTIF-CONTAINING GTPASE-ACTIVATING PROTEIN FAMILY IN LIVER CANCER - Agustriawan, David; Sumarpo, Anton; Parikesit, Arli Aditya; Nurdiansyah, Rizky; Adisurja, Gabriella Patricia; Ap, Ricky Ravindra Fajar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this paper is to identify the list of microRNA (miRNA) which can regulate the aberrant expression of IQGAP in liver cancer formation. The aberrant expression of IQ motif-containing GTPase-activating protein (IQGAP) family which consists of IQGAP1, IQGAP2, and IQGAP3 has been linked to carcinogenesis in human cancers. The reciprocal expression of IQGAP family in human cancer has been studied to act as oncogenes or tumor suppressor genes. A growing number of studies suggest that upregulated or downregulated expression of IQGAP family triggers cancer development. Methods: A correlation study was performed to construct a pathway to inhibit or activate IQGAP family between miRNAs and IQGAPs. A pre-processing step was conducted to download, filter and process the dataset from TCGA. It yields miRNA and IQGAP gene expression matrix. Then, correlation computation was computed using MATLAB. Moreover, this study linked the results to the MiRTarBase to validate the prediction result with the wet lab experimental result. Results: This study identified significantly inversely correlation in 51 miRNAs-IQGAP1, 169 miRNAs-IQGAP2, and 33 miRNAs-IQGAP3, respectively, which may potentially play a role in a liver cancer formation. Some of the results also can be found in miRTarBase. It supports the precision of those miRNA and IQGAP interaction between dry lab and wet lab study. IQGAP1 and IQGAP2 mostly has been identified as an oncogene in cancer but IQGAP2 has been discovered as tumor suppressor gene. The list of miRNA in the result of this study can become a potential therapy to target the aberrant expression of IQGAP family. Conclusion: miRNA function is known as an oncogene or tumor suppressor gene in cancer development. Therefore, it can be one of the important molecular biology which may target the aberrant expression of IQGAP in liver cancer.